2022
DOI: 10.1111/bjd.21276
|View full text |Cite
|
Sign up to set email alerts
|

Prognoses of patients with melanoma who continue/discontinue anti-programmed death-1 therapy after achieving a complete response in a real-world setting: a multicentre retrospective study

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…In contrast, several retrospective studies on melanoma have reported clinical outcomes after early discontinuation of ICI therapy. [66][67][68] In a real-world analysis of 185 patients with advanced melanoma who discontinued anti-PD-1 treatment in the absence of disease progression or treatment-limiting toxicity, 145 (78%) patients remained free from disease progression. Relapse after treatment discontinuation was infrequent in patients who achieved a CR and were treated for more than 6 months.…”
Section: Immune Checkpoint Inhibitorsmentioning
confidence: 99%
See 3 more Smart Citations
“…In contrast, several retrospective studies on melanoma have reported clinical outcomes after early discontinuation of ICI therapy. [66][67][68] In a real-world analysis of 185 patients with advanced melanoma who discontinued anti-PD-1 treatment in the absence of disease progression or treatment-limiting toxicity, 145 (78%) patients remained free from disease progression. Relapse after treatment discontinuation was infrequent in patients who achieved a CR and were treated for more than 6 months.…”
Section: Immune Checkpoint Inhibitorsmentioning
confidence: 99%
“…Importantly, this study included 12 patients with the acral subtype and 22 with the mucosal subtype, therefore, a sustained clinical benefit may occur regardless of the melanoma subtype. 68 Currently, there are several ongoing clinical trials to determine the optimal duration of ICI treatment for advanced melanoma (Table 2). The STOP-GAP trial in Canada is a randomized phase III trial comparing intermittent anti-PD-1 therapy with standard continuous anti-PD-1 therapy for up to 2 years.…”
Section: Immune Checkpoint Inhibitorsmentioning
confidence: 99%
See 2 more Smart Citations